Investigating the character of women in Attar's divine book, based on Bullen's psychological opinions - Mohammadi Sadr, Abdullah; Tajnia, Kimia; Eslami, Ismail (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aims to investigate and analyze the female characters of Masnavi Elahi-nameh by Attar Neishabouri; It has been done based on the psychological opinions of Bolen. In this poem, Attar has explained the character of women very well. Method: in terms of methodology, the current research method is library and descriptive-analytical. In this research, first, all the evidences in which there are female characters have been determined, and then by categorizing these evidences, analyzes have been added to them, and they have been examined based on the psychological opinions of Bolen. Results: The findings showed that Attar Nishabouri used different tools to process the characters of women. He has introduced these characters in two direct and indirect ways. In this system, Attar considers the origin and root of women to be purity and by introducing their identity, values such as chastity and chastity, truthfulness, the power of thinking and rationality, ignoring wealth and power, the power to make correct decisions, etc. .. has been introduced in the character of women and presented to his audience; Undoubtedly, applying these values in the family system and paying attention to them has a therapeutic role and leads to the improvement of human behavior. Conclusion: From the examination and criticism of the divine archetype of Attar's letter in the context of women, it was concluded that Attar's conscious soul, by looking deeply and searching the facts, was able to find the archetype of women and used them unconsciously in his poems. The story of "Zen Saliha" is one of the archetypal secret stories in which collective unconscious elements joined hands and played a special role in advancing the story and visualizing the original source. Jungian archetypal elements are clearly seen in this story. But the main archetype underlying this story is the demon archetype itself, which has been nurtured with the help of other archetypes. The ultimate winner of this battle is chastity and salvation.